2005
DOI: 10.1111/j.1742-7843.2005.pto_117.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Administration of and Tachyphylaxis to α,β‐Methylene ATP in the Guinea‐Pig Small Intestine

Abstract: Abstract:The aim of the present study was to assess the acute motility effects and desensitizing activity of the stable ATP analogue and P 2X purinoceptor agonist a,b-methylene ATP (a,b-meATP) and the effect of a,b-meATP desensitization on nerve-mediated cholinergic responses in the guinea-pig ileum in vitro. It was confirmed that a,b-meATP (1-30 mM) causes neurally-mediated, cholinergic (tetrodotoxin-and atropine-sensitive) longitudinal contractions. These responses were not influenced by the ganglionic block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Whereas with a dose of 1 μmol/l of αβ-methylene ATP, we did not find a significant alteration of the nicotine effects, an observation that had also been reported by Benkó et al [9] with even much high doses of this compound, we found that the P2X antagonist PPADS reduced the nicotine contraction and prevented the nicotine desensitization. On the other hand, it has been shown that hexamethonium has no effect on the αβ-methylene ATP contraction [9] .…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Whereas with a dose of 1 μmol/l of αβ-methylene ATP, we did not find a significant alteration of the nicotine effects, an observation that had also been reported by Benkó et al [9] with even much high doses of this compound, we found that the P2X antagonist PPADS reduced the nicotine contraction and prevented the nicotine desensitization. On the other hand, it has been shown that hexamethonium has no effect on the αβ-methylene ATP contraction [9] .…”
Section: Discussionsupporting
confidence: 66%
“…It has also already been reported by Benkó et al [9] that αβ-methylene ATP can reduce the cholinergic twitch to some extent, and this effect had been ascribed to some type of 'tachyphylaxis' on the motor neuron. The P2X ligand-gated ion channel allows the inflow of sodium and calcium ion, leading to depolarization and activation of calcium-sensitive intracellular processes [4] .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…At least in the mouse ileum, smooth muscle cells were strongly immunoreactive for P2Y 1 receptors [7] , and myenteric plexus neurons in the guinea-pig ileum were shown to express the P2Y 6 and P2Y 12 receptor [36] . However, interspecies differences are very likely, because α,β-Me-ATP-induced contractions of guinea-pig ileum were sensitive to the P2X 1 receptor antagonist NF279 and the P2X receptor-preferring blocker PPADS [37] . This finding is in contrast to the present results using rat ileum, which point to a predominant P2Y receptormediated contraction following exposure to α,β-Me-ATP.…”
Section: Wwwchinapharcom Mader F Et Almentioning
confidence: 99%